Self-Control and Fear of Missing Out Among University Students: Pengendalian Diri dan Rasa Takut Ketinggalan di Kalangan Mahasiswa - Lailatus Saniah; Zaki Nur Fahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid growth of social media use in the digital era has intensified psychological phenomena among university students, including fear of missing out (FoMO), which is associated with continuous online engagement and emotional responses to social information. Specific Background: Self-control is considered an important psychological capacity that enables individuals to regulate behavior, interpret stimuli, and manage social media usage to prevent excessive engagement. Knowledge Gap: Previous studies have reported inconsistent findings regarding the association between self-control and FoMO, particularly within university student populations, indicating the need for empirical clarification. Aims: This study aimed to examine the relationship between self-control and fear of missing out among FPIP students at Muhammadiyah University of Sidoarjo. Results: Using a quantitative correlational design involving 213 students, data were collected through validated self-control and FoMO scales and analyzed using a non-parametric correlation test with IBM SPSS Statistics 29. The findings showed a correlation coefficient of −0.176 with a significance value of 0.010 > 0.05, indicating no significant relationship between self-control and FoMO. Novelty: The study provides empirical evidence demonstrating the absence of a statistically significant association between self-control and FoMO within the examined student context, contributing to ongoing academic debate regarding psychological predictors of FoMO. Implications: These findings suggest that FoMO among university students may involve factors beyond self-control alone and highlight the importance of promoting balanced social media use and behavioral regulation strategies in higher education settings. Highlights: Statistical Testing Revealed a Non-Significant Association Between the Examined Psychological Variables. Student Participants Displayed Measurable FOMO Characteristics Despite Varying Regulatory Abilities. Empirical Evidence Contributes to Mixed Research Outcomes Reported in Prior Student-Based Studies. Keywords: Self-Control, Fear of Missing Out, University Students, Social Media Behavior, Quantitative Correlational Study